Kemas Haji Abdullah Azhari: Kontribusinya dalam Dinamika Perkembangan Tarekat Sammaniyah di Palembang (1304-1357/1889-1938) - Octaviani, Rindi; Amilda, Amilda; Padila, Padila (Program Studi Sejarah Peradaban Islamm UIN Raden Fatah Palembang, 2023)
This study explains the contribution of Kemas Haji Abdullah Azhari to the dynamics of the Sammaniyah tariqa in 1304-1357 H / 1889-1938 AD in Palembang. This study used qualitative data types. This study focused on answering the main problems, including the first, how to enter and develop the Sammaniyah tariqa in Palembang. Second, how did Kemas Haji Abdullah Azhari contribute to the dynamics of the Sammaniyah tariqa in Palembang in 1304-1357 H / 1889-1938 A.D. This research uses historical research methodology with four stages, namely: heuristics, source criticism, interpretation, and historiography. The source of the data used is first, an interview conducted with Zuriat, his work entitled genealogy and biography of Kemas Haji Abdullah Azhari. Meanwhile, secondary data are books, journals, and articles related to this study. The theory used in this study is the theory of social change developed by Talcot Parson and the role theory developed by Levinson.